DisORIENT: Money, Technological Development and the Rise of the West. (December 2016) - Vernengo, Matías; Fields, David
An extensive and important literature has shown that the Rise of the West occurred considerably later than often thought, only in the 19th century, and that the main advantages of the West prior to that period were essentially military. However, this revisionist literature fails to incorporate the insights of radical political economics, both regarding money and the role of demand in technological progress, in ways that distort their conclusions. This paper suggests that both revisionists and radical political economists would benefit from each other's insights.